Effect of listening to sedative music and Quranic recitations on stress level among IIUM undergraduate students - Norfatin Nabila Raduian (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The failure to cope well with the pressure of the university life will lead students to fall into prolonged stress. To reduce the proneness to stress, early prevention needs to be taken before it becomes harmful to the mental and physical health. The present study suggests that sound-based interventions such as listening to sedative music and Quranic recitations may be helpful in reducing the stress level. The purpose of the present study is to evaluate the effectiveness of two sound-based interventions i.e. (1) listening to sedative music and (2) listening to Quranic recitations on the stress level by measuring the stress levels during pre- and post-interventions. The study was carried out at the International Islamic University Malaysia (IIUM) among the undergraduate's level student (n=77). The researcher conducted brief socio-demographic survey and State Trait Anxiety Inventory (STAI) (form Y-1) (20 items) on the participants in the pre-intervention stage. Then, a stress induced task was conducted through a mental arithmetic task. Then, the interventions were given and once again the STAI were administered during post-intervention stage. The result highlighted that listening to Quranic recitations is more likely to reduce stress level than listening to sedative music and sitting in silence. Limitations, practical implications, as well suggestions for future research were also discussed.